Pengaruh Kepemimpinan dan Kompetensi terhadap Kinerja Karyawan PT Pratama Abadi Industri dengan Kepuasan Kerja sebagai Variabel Mediating - Cecep Haryoto; Hasanah Hasanah; Koen Adi Suryo (LPPM IAI Nasional Laa Roiba Bogor, 2024)
This research aims to test and analyze the influence of Leadership and Competency on Employee Performance with Job Satisfaction as a Mediating Variable at PT. Pratama Abadi Industri. The independent variables used are Leadership and Competence, while the dependent variables are Employee Performance and the mediating variable is Job Satisfaction. The data collection method in this research was carried out by distributing questionnaires to 150 respondents from employees at PT. Pratama Abadi Industri. The research method used is an associative quantitative method using primary data and the data analysis model used is Structural Equitional Modeling (SEM) using PLS.4. The results of this research show that leadership has a positive and significant effect on employee performance with a coefficient value of 0.411. Competence has a positive and significant effect on employee performance with a coefficient value of 0.182. Leadership has a positive and significant effect on Job Satisfaction with a coefficient value of 0.597. Competency has a positive and significant effect on Job Satisfaction with a coefficient value of 0.279. Leadership has a positive and significant effect on employee performance through job satisfaction with a coefficient value of 0.460. Competency has a positive and significant effect on employee performance through job satisfaction with a coefficient value of 0.253. Job Satisfaction has a positive and significant effect on Employee Performance with a coefficient value of 0.389.